Analisis Pendapatan Asli Daerah Kota & Kabupaten di Jawa Barat - Harmain, Indra; Tarmidi, Deden (Media Akuntansi Perpajakan, 2023)
Local revenue through Regional Original Revenue (PAD) is a very important revenue component for local governments, because it is related to the regional development process. The higher the PAD, the better the development will be, such as economic growth, poverty reduction and unemployment and the HDI will increase. Therefore, local taxes must be managed professionally and transparently in order to optimize and try to increase their contribution to the regional revenue and expenditure budget through PAD. The purpose of this study is to analyze where the sources of local revenue of cities and districts in West Java Province come from. With a unit of analysis of 135 data from 27 regencies / cities in West Java in 2018-2022, using multiple linear regression analysis, this study found a positive contribution from hotel tax, restaurant tax and billboard tax on local revenue of cities and districts in West Java province, while the contribution of entertainment tax was not significant.